From Furfural to Fuel: Synthesis of Furoins by Organocatalysis and their Hydrodeoxygenation by Cascade Catalysis. Issue 9 (1st August 2014) - Wegenhart, Benjamin L.; Yang, Linan; Kwan, Soon Cheong; Harris, Remi; Kenttämaa, Hilkka I.; Abu‐Omar, Mahdi M.
Abstract The synthesis of furoins from biomass‐derived furfural and 2‐methylfurfural is demonstrated in high yields in green and renewable solvents using N‐heterocyclic carbene organocatalysts. The resulting furoin molecules are used as precursors for fuels using cascade catalysis, first by using Pd/C with acidic co‐catalysts under very mild conditions to yield oxygenated C12 molecules. Two main products were formed, which we identified as 1, 2‐bis(5‐methyltetrahydrofuran‐2‐yl)ethane and 1‐(5‐methyltetrahydrofuran‐2‐yl)heptanol. The use of a Pd/Zeolite‐β catalyst under more extreme conditions resulted in the complete hydrodeoxygenation of 5, 5′‐dimethylfuroin to dodecanes in high yields (76 %) and exceptional selectivity (94 %) for n‐dodecane.